Unveiling Vannamei Shrimp Farming's Impact on Water Pollution in Wonocoyo Village - Rupiwardani, Irfany; Saktiawan, Yusup; Yohanan, Agus (Jurnal Pembangunan dan Alam Lestari, 2023)
Shrimp aquaculture has both positive and negative consequences if not properly managed. The recurring issue is the generation of waste, which affects the efficiency of fisheries utilization. Evaluation of utilization efficiency can be seen by estimating waste produced from the feed used during shrimp utilization, the optimal feed conversion ratio, and the resulting shrimp production rate. This research looks at the nutrient waste load originating from the semi-intensive utilization of vannamai shrimp in Wonocoyo Village. The research method employed is a quantitative descriptive approach. Primary data consists of water samples taken before and after receiving aquaculture waste. The waste content in both the pond water and the river water is measured in a laboratory. The calculation results demonstrate that the shrimp aquaculture facilities in Wonocoyo Village, Trenggalek Regency, produce waste with relatively minor environmental impacts. However, if the number of aquaculture plots increases, the environmental impact will also rise. Keywords: shrimp farm, semi-intensive, nutrient waste load